Pengaruh Website Design, Informativeness, dan Security of Online Transaction terhadap Customer Satisfaction - Nurlina Bangun; Aisyah (Jurnal ISIP: Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
This article was written based on the results of research on the influence of website design, informativeness, and security of online transactions through the website on the customer satisfaction. The website researched is www.ucareindonesia.org which is organized by the Ukhuwah Care Indonesia Institute as an Amil Zakat Institution in Bekasi City. The method used is a survey of Ucare Indonesia customers (visitors) on the website www.ucareindonesia.org with the multiple linear regression analysis techniques. The sample was selected using a the purposive technique with the criteria being an active customer to donate. The results showed that the website design and informativeness of www.ucare indonesia.org had an effect on customer satisfaction. However, the security of online transaction website variable has no effect. The contribution of the influence of the three variables simultaneously is equal to 57%.